Injectable self-gelling composites for bone tissue engineering based on gellan gum hydrogel enriched with different bioglasses - Douglas, Timothy E. L.; Piwowarczyk, Wojciech; Pamula, Elzbieta; Liskova, Jana; Schaubroeck, David; Leeuwenburgh, Sander C. G.; Brackman, Gilles; Balcaen, Lieve; Detsch, Rainer; Declercq, Heidi; Cholewa-Kowalska, Katarzyna; Dokupil, Agnieszka; et al. (Biomedical Materials (Bristol), 2014)
Hydrogels of biocompatible calcium-crosslinkable polysaccharide gellan gum (GG) were enriched with bioglass particles to enhance (i) mineralization with calcium phosphate (CaP); (ii) antibacterial properties and (iii) growth of bone-forming cells for future bone regeneration applications. Three bioglasses were compared, namely one calcium-rich and one calcium-poor preparation both produced by a sol-gel technique (hereafter referred to as A2 and S2, respectively) and one preparation of composition close to that of the commonly used 45S5 type (hereafter referred to as NBG). Incubation in SBF for 7 d, 14 d and 21 d caused apatite formation in bioglass-containing but not in bioglass-free samples, as confirmed by FTIR, XRD, SEM, ICP-OES, and measurements of dry mass, i.e. mass attributable to polymer and mineral and not water. Mechanical testing revealed an increase in compressive modulus in samples containing S2 and NBG but not A2. Antibacterial testing using biofilm-forming meticillin-resistant staphylococcus aureus (MRSA) showed markedly higher antibacterial activity of samples containing A2 and S2 than samples containing NBG and bioglass-free samples. Cell biological characterization using rat mesenchymal stem cells (rMSCs) revealed a stimulatory effect of NBG on rMSC differentiation. The addition of bioglass thus promotes GG mineralizability and, depending on bioglass type, antibacterial properties and rMSC differentiation. © 2014 IOP Publishing Ltd.
Keywords: bioglass; bone tissue engineering; gellan gum; hydrogel; injectable; osteoblast